Crossing Borders: On erroneous expressions in public space – Results of a linguistic landscape research project - Dargiewicz, Anna (Papers in Linguistics, 2026)
Linguistic landscape concerns visually designed language in public spaces. The city is not only a place of oral communication, but also a place where people communicate by means of the written word (cf. Metten 2011: 90). Texts present in public spaces demonstrate boundless creativity of language users, as confirmed by the corpus obtained through linguistic landscape research in German public space. This creativity is reflected in linguistic forms that are striking, surprising or thought-provoking due to their peculiarity, a feature that attracts viewers’ attention. They are often new linguistic formations, proving that language users apply various methods of combining words/word-forming morphemes in order to communicate in interesting, previously unfamiliar ways. As a result, the information to be communicated undoubtedly attracts increased attention of the recipient. However, incorrect expressions that can be found in the analysed public texts also attract attention. Unfortunately, people do not always make sure that the content that appears in urban space is linguistically correct. This is a major disadvantage as regards this sort of texts and their goal to serve our common good. The aim of the article is to reflect on the problem of erroneous expressions that occur in texts appearing in the public sphere on the basis of the results of a corpus-based empirical study.